Analisis Pengaruh Keterbukaan Perdagangan, Konsumsi Energi, dan Pertumbuhan Ekonomi terhadap Emisi Karbon di Negara D-8 - Siregar, Suci Wulandari; Hasbi (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2023)
Carbon emissions are one of the main causes of global climate change. High carbon emissions can hinder long-term economic growth. The purpose of this research is to analyze the influence of Trade Openness, Energy Consumption, and Economic Growth variables on CO2 Emissions in D-8 countries (Bangladesh, Egypt, Indonesia, Iran, Malaysia, Nigeria, Pakistan, and Turkey) during the period of 1992 to 2021 using the Autoregressive Distributed Lag (ARDL) panel model. The results of the study indicate that Economic Growth in D-8 countries has a positive long-term effect on CO2 Emissions but has no short-term effect. The Energy Consumption variable has a short-term effect on CO2 Emissions. However, Trade Openness does not have a short-term or long-term effect on CO2 Emissions. Therefore, it is expected that D-8 countries pay attention to policies that encourage investment in renewable energy, incentives for energy efficiency, and regulations that reduce emissions from specific sectors, which can help achieve sustainable and low-carbon economic growth.